Determining the relationship among laboratory satisfaction, motivated learning strategies, and performance of distance animal anatomy and physiology students and comparing their performance to on-campus students - Crabtree, Celsey J. (Kansas State University, 2022)
Distance courses are in high demand, post-secondary institutions are being encouraged to offer more. Some studies have found distance science classes to be as effective in content and student success, as on-campus courses. Distance courses often require greater self-motivation and study skills and as a result, the success of students in distance courses may be more variable than what would normally be found in on-campus courses. To assess the role of student preparation and learning characteristics in a distance version of a senior-level college anatomy and physiology course the Motivated Strategies for Learning Questionnaire (MSLQ) was used to examine the relationship between motivation, self-regulated learning, and academic achievement in an online animal anatomy and physiology laboratory section. The online laboratory section ran in conjunction with an online lecture course and enrollment in both was required. The online laboratory section was compared to an on-campus laboratory section. A pre- and post-test was administered to students to determine knowledge gained and compared distance and on-campus scores. Additionally, distance student satisfaction was measured using a self-reporting Likert Scale survey. The Motivation section of the MSLQ is intended to assess value, expectancy, and affect as reported by students. The Learning Strategies section is intended to assess use of cognitive, metacognitive, and resource management strategies. Construct mean scores were correlated with end of lab grades. Data from each semester, Spring 2021 and Fall 2021, were analyzed separately. Distance students from both semesters reported self-efficacy, task value, and help-seeking strategies were correlated to their final laboratory grade. In contrast, on-campus students reported control of learning beliefs, and self-efficacy to be correlated with their final laboratory grades. There were variations between semesters in effectiveness of distance learning based on improvement in pre-test versus post-test scores given at the beginning and ending of the semester, respectively. Both semesters of distance students improved their anatomy knowledge more than the on-campus students. When compared to the distance students in Fall 2021, Spring 2021 distance students spent more hours completing laboratory assignments, worked more hours per week, and were enrolled in more credit hours. Both semesters of distance students were overall satisfied with their experiences but Fall 2021 students rated the course satisfaction higher, which indicated distance students can be highly satisfied with distance laboratory courses. The differences in demographics could partially explain the differences in satisfaction scores between the two semesters as students in the distance Fall 2021 course reported overall a higher satisfaction score. Additionally, both semesters of distance students gained more anatomy knowledge when compared to the on-campus students, indicating mode of delivery was just as effective. Furthermore, each group of students reported different constructs that influenced academic performance, but majority of students reported that self-efficacy influenced academic performance. Students in the fall distance and on-campus courses did have similar motivations and learning strategies, such as task value and self-efficacy which are two components of self-regulated learning, that positively predict student satisfaction which could explain their overall satisfaction with the course. Additionally, the higher correlations with the MSLQ constructs and final laboratory grade could explain the knowledge gained in the fall semester. Instructors could use known motivations to improve learning in the classroom despite mode of delivery and educate students about self-reflection and self-regulation methods. Instructors could provide students opportunities to self-assess efforts. Lastly, Animal Science programs can offer distance specific science classes and instructors should be encouraged to explore opportunities to expand their programs using at-home laboratory kits that give students hands-on experiences.
Keywords: Distance education; Animal science; Laboratory education; Laboratory performance